2016
DOI: 10.1002/aoc.3659
|View full text |Cite
|
Sign up to set email alerts
|

MnO2/graphene oxide: A highly efficient catalyst for imine synthesis from alcohols and amines

Abstract: α‐MnO2 nanocrystals supported on graphene oxide (α‐MnO2/GO) was prepared through a soft chemical route and evaluated for the first time as a novel, eco‐friendly and efficient catalyst in the coupling reaction of alcohols and amines to imines. The well‐organized α‐MnO2/GO was characterized using various techniques. The results show that MnO2 nanocrystals are highly dispersed on the GO sheets and interconnected with each other, leading to large available surface area, which greatly enhances the catalytic perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…For example, chromium-based reagents are toxic, irritants and corrosive; whereas manganese dioxide (MnO 2 ), being more environment-friendly, has been used over the years as a highly efficient and selective catalyst for oxidation of allylic and benzylic alcohols to aldehydes, amines to imines, oxidation of CO, H 2 O 2 decomposition, oxygen reduction, oligomerization of methane… [19,55,[60][61][62][63][64] Table 2 includes the most important results obtained with K-OMS2, [Ru]-K-OMS2 (2 wt%) as well as other related oxides as catalysts for the sele ctive synthesis of benzaldehyde from benzyl alcohol as model reaction.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…For example, chromium-based reagents are toxic, irritants and corrosive; whereas manganese dioxide (MnO 2 ), being more environment-friendly, has been used over the years as a highly efficient and selective catalyst for oxidation of allylic and benzylic alcohols to aldehydes, amines to imines, oxidation of CO, H 2 O 2 decomposition, oxygen reduction, oligomerization of methane… [19,55,[60][61][62][63][64] Table 2 includes the most important results obtained with K-OMS2, [Ru]-K-OMS2 (2 wt%) as well as other related oxides as catalysts for the sele ctive synthesis of benzaldehyde from benzyl alcohol as model reaction.…”
Section: Catalytic Activitymentioning
confidence: 99%
“…Cheng et al [ 196 ] reported the synthesis of imines from one‐pot multicomponent condensation reaction of benzyl alcohol, aniline by using α‐MnO 2 /GO (0.010 g) as a catalyst with O 2 balloon, and toluene as a solvent system at 110°C for 6–8 h (Scheme 31). To optimize the reaction conditions, different solvents were tested such as toluene, DMF, EtOH, THF, and MeCN, but the use of toluene at 110°C gave excellent yields (76% to 96%).…”
Section: Go‐supported Metal Oxides As Catalystmentioning
confidence: 99%
“…1 By having an active CN bond, imines are key intermediates in the synthesis of pharmaceuticals, fine chemicals, and biologically active heterocyclic compounds, such as α-amino acids and α-amino alcohols. 2 Imine reactivity includes reduction, addition, condensation, and multicomponent reactions. 3,4 Several synthetic routes are described in the literature for imine synthesis.…”
Section: ■ Introductionmentioning
confidence: 99%